Topological Organic Chemistry: From Distance Matrix to Timisoara Eccentricity - V. Putz, Mihai; A. Tudoran, Marina; Ori, Ottorino (Current Organic Chemistry, 2015)
This work presents chemical applications of topological methods in various sectors, from small molecule to biological systems, in studying for example enzyme-catalyzed reaction, protein folding kinetics, DNA sequence characterization. Topological descriptors participate to QSAR/QSPR models and, furthermore, are able to individuate the regions which are stabilized (or, vice versa, made reactive) by certain topological interactions. The Wiener indexes, and other distance-based invariants, constrained by the minimum-principle, oppose any unfavorable topological variation in the molecular structure (e.g. chemical transformations). Topological models characterize therefore chemical structures with astonishing details with computational simplicity predicting novel chemical mechanisms to be confirmed by subsequent ab-initio studies. Reported topological methods for simulating complex chemical mechanism and interesting chemical structures preserve the “usual” computational simplicity and still carry a large amount of chemical information stored in topology, an evident alliance between chemistry and mathematics in explaining how the nano-world works.
Keywords: Timisoara eccentricity